Étoile Errante, de J.M.G. Le Clézio: L’Histoire dé-historisée - Maria da Conceição Carrilho (Carnets)
Written in 1992, can this novel, – that tells the story of a girl who flees across second – world- war Europe in the company of her mother –, be considered another tragic novel, like countless others that explore this same subject, or is it a “Le Clezio” novel, that is to say, a novel whose main purpose is to praise life and the beauty of the world? The distinct development given to the following themes allows us to answer affirmatively to this question: the presence of a child-hero (adolescent), whose contemplative nature is much stronger than her rebelliousness; the exile, considered as a possibility of meetings and opening up to the world rather than as an experience of loss and death; and, finally, the memory, which, following in the stoic tradition that characterizes this writer’s philosophy, is considered a movement of capture of a cosmic sense, rather than a reservoir of traumatic experiences.